Od redakcji - Jarzyna, Anita; Kovacheva, Adriana; Kuczyńska-Koschany, Katarzyna; Rajewska, Ewa; Jaworski, Marcin; Śniedziewski, Piotr (Poznańskie Studia Polonistyczne. Seria Literacka, 2014)
Wstęp redakcji do tomu zatytułowanego Wyobraźnia w przekładzie.